Development of the banking system of Ukraine in the light of experience of chinese economic reforms - Т. V. Chelombitko (Вісник Харківського національного університету імені В.Н. Каразіна: Серія Економіка, 2018)
The article defines development trends and negative processes that determine the current state of the banking sector of the Ukrainian economy. The main indicators of the activity of the domestic banking system, including the volume of deposit funds, deductions to reserves, credit indebtedness and the dynamics of the growth of bank capital, are analyzed. In parallel with the analysis of the domestic banking system, the state of China's banking industry and the main results of reforming and developing of the Chinese economy were examined. The role of the banking system in overcoming crisis phenomena as the main factor in stabilizing the Chinese economy is disclosed. The directions of using the experience of China in the sphere of strengthening the domestic banking system and state stimulation of Ukraine's economic development are proposed. Priority ways of renewing the efficiency of the domestic banking sector have been formulated, which include overcoming macroeconomic imbalances, correcting monetary policy mistakes, introducing an effective risk management system against the loss and depreciation of investors' capital, adjusting credit policies to minimize risks, and strengthening the role of prudential supervision in Ukraine.